HUMANITY IN THE SYSTEM OF ANTHROPOLOGICAL DIMENSIONS OF MODERN COMMUNICATIVE PROCESSES - Mokliak, Larysa (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2025)
The 21st-century anthropological catastrophe at the heart of European civilization has intensified the need to rethink not only economic and political but also moral and value foundations of man’s existence. The aim of the article is to find out the basis on which the internal spiritual community of the participants of communicative processes is being formed. Research methods. The study is based on the dialectical method of research, combined with general scientific methods such as the systematic, cultural-historical, and comparative methods. The use of conceptual and terminological analysis enables the identification of the essential characteristics of the concept of "humanity" in relation to categories such as "spirituality," "morality," "compassion," and “understanding." The aim of the article is to find out the basis on which the internal spiritual community of the participants of communicative processes is formed. Research results. To single out the anthropological factor, the value-based point of reference, which enables a person, in relation to other representatives of their coexistence, to move from the level of "I-It relationship"(a cognitively pragmatic world, where a person performs a certain utilitarian function, being in a monologic, individualized world) to the level of "I-You relationship" (a dialogical connection that ensures the realization of full-fledged interpersonal relations). Discussion. Among the wide range of anthropological dimensions of communicative processes, the concept of "humanity" deserves special attention. Involvement of the conceptual analysis allows to determine the essential characteristics of the concept "humanity" in relation to such categories as "spirituality", "morality", "compassion" and "understanding". Conclusions. Humanity, as a worldview-regulatory reference point of a person, is a conscious moral principle that is created and formed in the process of real-life activities of social subjects. When the imperative instructions of morality as a sphere of general duty are transformed into personal convictions, they become spiritual and mental phenomena and regulators, shaping the world of individuals, social groups, communities, families, ethnicities, nations, and society as a whole. The article substantiates the opinion that dialogic communication can be carried out only when its participants establish partner relations, which have signs of humanity in their core